2022
DOI: 10.1039/d2dt01659a
|View full text |Cite
|
Sign up to set email alerts
|

One pot three component synthesis of DNA targeting phototoxic Ru(ii)-p-cymene dipyrido[3,2-a:2′,3′-c]phenazine analogues

Abstract: We have developed a One pot three component synthetic protocol for half-sandwich Ru(II)-p-cymene dipyrido[3,2-a:2',3'-c]phenazine analogues for selective cancer therapy under light irradiation. On average, the cytotoxicity of all the complexes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
3
11
0
Order By: Relevance
“…On the other hand, the protons in the para position as well as the phenazine protons remained largely unaffected. Similar observations were previously reported for other Ru-dppz complexes . For example, in the uncoordinated ligand A , the signals of H2(H2′) and H4(H4′) protons appeared at 9.47 and 9.16 ppm, respectively.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…On the other hand, the protons in the para position as well as the phenazine protons remained largely unaffected. Similar observations were previously reported for other Ru-dppz complexes . For example, in the uncoordinated ligand A , the signals of H2(H2′) and H4(H4′) protons appeared at 9.47 and 9.16 ppm, respectively.…”
Section: Resultssupporting
confidence: 89%
“…The observed isotopic distribution pattern was in good agreement with the calculated mass distribution. Analysis of the NMR spectra revealed that the chemical shifts of the protons and carbons of the Ru complexes were in agreement with the previously published structurally similar compounds. , As expected, the arene-to-ligand ratio was found to be 1:1 as determined by the integration of protons in the 1 H NMR spectra. The six protons originated from the benzene moiety in complexes 1A – 1C were located at 6.35 ppm.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations